Empirical estimates of fiscal multipliers for South Africa - Johannes Hermanus Kemp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Despite the frequent use of fiscal policy for stabilization purposes and the important role fiscal activism has played over the last decade, the size of budgetary multipliers (i.e. the output response following an exogenous shock to fiscal policy) has been heatedly debated at the theoretical and empirical levels, both globally and in the South African context. This paper estimates fiscal multipliers for South Africa using a variety of identification approaches and model specifications. The main findings show that the size of budgetary multipliers is sensitive to the identification strategy and modelling approach used. Keeping this caveat in mind, the estimation results show that government spending multipliers are positive, albeit generally smaller than 1. In contrast, tax multipliers are large and distortionary. It is also shown that both spending and tax multipliers are larger when the economy is in a recessionary state (or downswing).
Keywords: B22; E62; H62; H63; 330; fiscal multiplier; fiscal policy; state-dependent; structural VAR